Effect of Supplementation of Eucalyptus (Eucalyptus globulus) Leaf Powder in Diet Containing Phytase Enzyme on Performance of Commercial Laying Hens - Kaur, Manveen; Kumar, Ripusudan; Mondal, Bidhan C.; Siddiqui, Rukkiya; Kumar, Ashoka; Palod, Jyoti; Manjulata,; Kumar, Sudhir (Indian Journal of Veterinary Sciences and Biotechnology, 2022)
A feeding trial was conducted to discern the influence of dietary incorporation of eucalyptus (Eucalyptus globulus) leaf powder on  nutrient utilization, egg quality, and haemato-biochemical parameters of White Leghorn laying hens for 12 weeks. A total of 72, twenty eight days old laying hens were randomly assigned into four treatment groups, with 18 hens per treatment having three replicates of  6 birds each. Four treatment groups were control (T1): basal diet and Treatment T2, T3, and T4 with the incorporation of 0.30, 0.45, and  0.60 % eucalyptus leaf powder, respectively, in a basal diet containing phytase @250 FTU/kg feed. Results showed a significant (p
Keywords: Blood profile Eucalyptus leaf; Nutrient utilization; Phytase; Production performance; White Leghorn laying hens